2010
DOI: 10.1186/1752-1947-4-115
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoinfarction pattern in a patient with hyperkalemia, diabetic ketoacidosis and normal coronary vessels: a case report

Abstract: IntroductionA rare electrocardiographic finding of hyperkalemia is ST segment elevation or the so called 'pseudoinfarction' pattern. It has been suggested that hyperkalemia causes the 'pseudoinfarction' pattern not only through its direct myocardial effects, but also through other mechanisms, such as anoxia, acidosis, and coronary artery spasm.Case presentationA 33-year-old Caucasian woman with insulin-treated diabetes presented with continuous epigastric pain of four hours duration. Her coronary heart disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 8 publications
2
21
1
Order By: Relevance
“…ST segment elevation was also described as a rare manifestation of hyperkalemia in humans (most frequently in patients with diabetic ketoacidosis) where the ECG findings can resemble acute myocardial infarction and have therefore been described as pseudoinfarct or pseudoinjury ECG pattern . The mechanisms for hyperkalemia associated ST segment elevation in humans are not well understood, but repolarization abnormalities and other concurrent metabolic abnormalities such as acidosis have been discussed …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…ST segment elevation was also described as a rare manifestation of hyperkalemia in humans (most frequently in patients with diabetic ketoacidosis) where the ECG findings can resemble acute myocardial infarction and have therefore been described as pseudoinfarct or pseudoinjury ECG pattern . The mechanisms for hyperkalemia associated ST segment elevation in humans are not well understood, but repolarization abnormalities and other concurrent metabolic abnormalities such as acidosis have been discussed …”
Section: Discussionsupporting
confidence: 91%
“…60,61 The mechanisms for hyperkalemia associated ST segment elevation in humans are not well understood, but repolarization abnormalities and other concurrent metabolic abnormalities such as acidosis have been discussed. 62 Although typical ECG abnormalities were seen in hyperkalemic calves of our study population, bradycardia, or bradyarrhythmia was a rare finding in calves with increases in cK 1 . There was also no association between heart rate and cK 1 , which is in agreement to previous clinical studies in diarrheic calves as well as dogs and cats who also found no significant relationship 63,64 or even a slight positive association.…”
Section: Thismentioning
confidence: 54%
“…interpreting this data as a whole is limited given incomplete reporting of data in prior cases. Many of these reports theorize that the resolution of these ECG findings correlated with significant corrections in patient potassium levels [3,[6][7][8][10][11]. This specific case demonstrated normalization of the patient's ECG with clinically insignificant improvement in serum potassium levels.…”
Section: Figure 1: Initial Electrocardiogram Obtained Upon Arrival Tomentioning
confidence: 77%
“…There is increasingly documented phenomenon of pseudo-myocardial infarction that needs to be considered especially in those cases where the thrombolytic therapy has disastrous consequences. EKG changes compatible with acute myocardial infarction have been reported in association with Acute Abdomen, presenting with pancreatitis, gangrenous appendix, perforated duodenal ulcer, rectus sheath hematoma, and sepsis with shock (1) .Pseudo-myocardial infarction pattern has also been demonstrated in relation to diabetic Ketoacidosis (2) , Intracellular shift of potassium, Pulmonary embolism & Adrenergic hyper stimulation; all cases lead to picture of sick cardiomyocytes mimicking an injury current seen -Myocardial Infarction Necrosis. (3) The possible mechanism by which myocardial pseudo infarct occurs is unclear.…”
Section: Discussionmentioning
confidence: 99%